OPTIMASI FORMULA TABLET EFFERVESCENT EKSTRAK RIMPANG JAHE MERAH (Zingiber officinale Roxb. Var rubrum) - Henny Dwi Arini; Lannie Hadisoewignyo (Sanata Dharma University, 2012)
Abstract:This study aims to determine the effect of sodium citrate and fumaric acid as a source ofacid in the tablet formula effervescent red ginger rhizome extract (Zingiber officinale Roxb. varrubrum) and obtain the optimum composition of the formula that has the physical properties oftablet effervescent red ginger rhizome extract (Zingiber officinale Roxb. var rubrum) that meetthe requirements. Optimization techniques used in research is a method of factorial design withtwo factors and two levels of sodium citrate and fumaric acid with low levels of 80 mg, and highlevels of 120 mg. Responses were observed to obtain optimum formula is hardness, friability, andthe soluble tablet (effervescent time). The result is the concentration of sodium citrate andfumaric acid did not significantly affect tablet hardness effervescent. Meanwhile, that issignificantly influences the friability and time effervescent soluble tablets. However, theinteraction between sodium citrate and fumaric acid did not significantly affect the hardness,friability, and the soluble tablet effervescent red giinger extract. Optimum formula tabletsobtained effervescent namely sodium citrate 80 mg and 80 mg of fumaric acid with 6,529 kgfresponse tablet hardness, tablet friability 0,1354%, and effervescent time of 5,98 minutes.Key words : Red ginger, effervescent tablet, factorial design